Synthesis of Carbon‐Supported Pt–YOx and PtY Nanoparticles with High Catalytic Activity for the Oxygen Reduction Reaction Using a Microwave‐based Polyol Method. Issue 6 (20th February 2017) - Tsuji, Masaharu; Uto, Keiko; Nagami, Tetsuo; Muto, Akiko; Fukushima, Hideoki; Hayashi, Jun‐ichiro
Abstract: Carbon‐supported PtY alloy nanoparticles were prepared as oxygen reduction reaction (ORR) catalysts by reducing a mixture of cis ‐[Pt(NH3 )2 (NO2 )2 ] or Pt(C5 H7 O2 )2 and Y(CH3 COO)3 ⋅ 4 H2 O in ethylene glycol (EG) with microwave (MW) heating. Microstructure and composition analyses of products by using TEM, TEM–energy‐dispersive X‐ray spectroscopy (EDS), XRD, X‐ray photoelectron spectroscopy (XPS), and inductively coupled plasma atomic emission spectroscopy (ICP‐AES) data showed that Pt–YO x /C (Y/Pt=0.11–0.75) catalysts involving amorphous yttrium oxide were formed as major products. When the YO x component in the catalysts was removed by using HNO3 treatment, Pt99.1–99.6 Y0.4–0.9 /C alloy catalysts with low Y contents remained. Higher ORR activity was shown by Pt–YO x /C and PtY/C catalysts than by Pt–Y(OH)3 /C, Pt–YO x /C, or PtY/C catalysts prepared by using other conventional chemical reduction methods and thermal treatment methods under a H2 /Ar or Ar atmosphere. The mass activity (MA) and surface specific activity (SA) of the best Pt99.5 Y0.5 /C catalyst, MA=245 A gPt −1 and SA=711 μA cmPt −2, were equal to or higher than those of the commercially used Pt86 Co14 /C catalyst, MA=245 A gPt −1 and SA=512 μA cmPt −2 . The major reasons for the high ORR activity of these Pt–YO x /C and PtY catalysts are discussed. These Pt99.1–99.6 Y0.4–0.9 /C alloy catalysts prepared by using acid treatment are new and promising catalysts for use in proton exchange membrane fuel cells (PEMFCs). Abstract : Reducing O2 with Pt and Y : Carbon‐supported PtY alloy nanoparticles with a high catalytic activity for the oxygen reduction reaction were prepared by reducing mixtures of Pt and Y reagents in ethylene glycol under microwave heating, followed by HNO3 treatment. They are promising new catalysts for use in proton exchange membrane fuel cells.